Report on pitch perception experiments carried out in Buganda and Busoga (Uganda) - Cooke, Peter (International Library of African Music, 1992)
There is a relatively long history of scholarly interest in the tuning of different musical pitch systems that African peoples have evolved for their music making. One notable contribution is the pioneer effort of Hugh Tracey from the 1930s to the 1960s with his large set of tuning forks which he used for matching the pitches of many of the African instruments he recorded. Since then many of the pages of successive issues of African Music have contained tables of tunings for xylophones, harps, mbiras and such like instruments.
Keywords: African Music; Uganda; Buganda; Busoga